The Influence of The Principal's Leadership Behavior and Work Discipline on The Student’s Religiosity of MI 1 NWDI Pancor East Lombok - Taufiqurrahman, Lalu; Al Idrus, H.S. Ali Jadid; Muktar, Fathurrahman (JESS (Journal of Educational Social Studies), 2023)
This study aims to determine the effect of principal leadership and work discipline on student’s religiosity. This study uses a quantitative approach with the type of survey research and cross-sectional survey research design. Data collection using a questionnaire with a research population of all 6th grade students MI 1 NWDI Pancor East Lombok which amounted to 56 people. Data analysis techniques with validity, reliability, prerequisite tests, and hypothesis testing by means of bivariate and simultaneous tests. The results showed that there was an influence of the principal's leadership on the religiosity of MI 1 NWDI Pancor East Lombok students with a medium category r value is 0.520; there was an influence of work discipline on student’s religiosity with a medium category r value is 0.393; there was an influence of the principal's leadership on student religiosity was significant with a t value is 4.473> t table 2.000; there is an effect of work discipline on student’s religiosity is significant with a t value is 3.139> t table 2.000, simultaneously the effect of principal leadership and work discipline on student religiosity is significant with an F value is 13.985 and a significance is 0. 000013 < 0,05.